Enhancement of agro-pastoral productions in the rural community of M’Nahba (Wilaya of Marrakech – Morocco) - Lubino M.; Mortaji M.; Porqueddu C.; Sitzia M.; Roggero P.P.; Melis R. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Livelihood in rural communities of Morocco is based primarily on breeding of meat sheep in agropastoral systems where forage resources are scarce and mainly represented by cereal residuals and fallow. Intensive sheep grazing and frequent agricultural tillage on cereals, practiced by rural population as a consequence of the abandonment of nomadic life, have progressively contributed to serious soil degradation and erosion. This degradation of the ecosystem has been leading a rural exodus towards urban areas within and outside the country. The present contribution is devoted to illustrate the holistic approach and activities carried out by a bilateral cooperation project Sardinia-Morocco aimed at the rehabilitation of degraded pastures by means of alley cropping, the enhancement of socio-economic conditions and the exchange of knowledge and know-how between Sardinian and Moroccan stakeholders.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)